Selection of Video on Demand Service Applications for Students Using TOPSIS - Wandhansari Sekar Jatiningrum; Setya Khusna Rossy Pertiwi; Mohamad Irvan Irianto; Yolanda Okta Ria (OPSI, 2021)
Video on Demand service is getting popular for people to watch film or drama recently. Various streaming applications with different services and characteristics can be chosen by people. Students, as the largest consumers of film and drama industry, have various factors to be considered in choosing alternatives to these streaming services. This study aims to enable users, namely students, to choose the best alternative among various choices of streaming service applications by consider several factors at once. TOPSIS method (Technique for Others Reference by Similarity to Ideal Solution) is used in this research to rank streaming service applications according to user preferences. The criteria considered by users are subscription fees, variety of film and drama choices, application views, and services provided. Data collection was carried out by distributing questionnaires to 50 student respondents regarding the criteria and alternatives. The results of TOPSIS analysis showed that students prefer Viu application as the best choice for watching films and dramas. The second to forth rankings are iflix, Netflix, and WeTV, respectively.